Analisis CSR: pentingnya etika pemasaran dan tanggung jawab sosial - Rohmah, Sabana; Afifudin, Arief (Maliki Interdisciplinary Journal, 2025)
Marketing ethics and corporate social responsibility (CSR) are two important, interrelated components of modern business practice. Corporate social responsibility includes the moral principles and values ​​that guide a company's behavior when promoting goods and services to consumers with the aim of ensuring transparency, honesty and respect for consumer rights. In contrast, CSR is a term that refers to a company's commitment to doing good things for society and the environment beyond purely economic interests. Strong marketing ethics help companies build consumer trust, improve brand image, and reduce the risk of an unfavorable reputation. However, a social responsibility (CSR) strategy is very important to support business sustainability through development programs, reducing community carbon emissions, and environmentally friendly product innovation. By working together with marketing ethics and CSR, business practices can be carried out holistically by considering profits and social and environmental desires. This study investigates the relationship between these two ideas, the variables that influence their implementation, and how they impact business success and public trust. The results show that the application of marketing ethics and CSR increases a company's competitiveness and encourages fairer and more sustainable business practices.